Identity struggle, professional development and career: A career/life history of a human resource management professional - Peticca-Harris, A.; McKenna, Stephen (Emerald Group Publishing, 2013)
Purpose: Through a single-person career/life history of a human resource (HR) manager, the purpose of this paper is to illuminate the relationship between professional identity and "being" a manager in the context of a "whole life". Design/methodology/approach: The approach of this paper is to use an extended interview with a single HR management professional to consider the complexities and discontinuities of managing a professional and personal life. The interview is considered in light of Alvesson's seven images of self-identity. Findings: Managers are constantly negotiating a professional identity, "being" a manager and a career in the context of their whole life. In developing managers in an increasingly stressful and competitive environment, the intersection between the various elements of a manager's life should be taken into account. Research limitations/implications: Closer attention should be paid to the lives of managers in the context of their identity and careers. Research should more closely consider, in detail, the lived experiences of managers and professionals. Practical implications: Management development should focus on lived experiences of managers rather than competency and skill development. Managerial performance is related to the coping and sensemaking that occurs within specific contexts and management development professionals should focus more on these aspects of a "managerial life". Originality/value: The value of the paper is in highlighting the importance of very focussed and very personal management development.